2014
DOI: 10.1111/cobi.12263
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Children's Conservation Biology Learning at the Zoo

Abstract: 2Millions of children visit zoos every year with parents or schools to encounter wildlife 3 firsthand. Public conservation education is a basic requirement for membership in 4 professional zoo associations. However, in recent years there has been increasing 5 criticism of zoos from animal rights groups for failing to demonstrate their averred 6 value for public understanding of conservation and related biological concepts such as 7 animal adaptation to habitats. Indeed, no full-scale study to date has rigorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 14 publications
(17 reference statements)
2
64
0
3
Order By: Relevance
“…This finding contrasts with Falk et al's (2007) claim that such factors are not important predictors of educational impacts. We found that, in fact, a combination of demographic and within-visit variables predicted the likelihood of improvements in visitors' biodiversity literacy (also see Jensen 2014). Future research should further inform our understanding of "complexity, change over time, and the interwoven and developmental nature of sociocultural variables influencing visitors' appropriation of new ideas" relating to biodiversity and conservation (Dawson & Jensen 2011:137).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This finding contrasts with Falk et al's (2007) claim that such factors are not important predictors of educational impacts. We found that, in fact, a combination of demographic and within-visit variables predicted the likelihood of improvements in visitors' biodiversity literacy (also see Jensen 2014). Future research should further inform our understanding of "complexity, change over time, and the interwoven and developmental nature of sociocultural variables influencing visitors' appropriation of new ideas" relating to biodiversity and conservation (Dawson & Jensen 2011:137).…”
Section: Discussionmentioning
confidence: 75%
“…The largest (N = 3018) single‐zoo visitor study to date is a repeated‐measures impact evaluation conducted with schoolchildren 7‐ to 15‐years old visiting London Zoo. Results of this study showed significant aggregate increases in biodiversity‐related learning after a visit to the zoo (Wagoner & Jensen , ; Jensen ). A multi‐institutional research program in the United States (Falk et al ) is probably the largest study of adult visitors to date.…”
Section: Introductionmentioning
confidence: 80%
“…), the world's zoos and aquariums are well positioned to contribute to achieving this target (Figure ). Indeed, recent studies have demonstrated the potential educational impacts of these institutions (eg Wagoner and Jensen , ; Jensen ). Additionally, the majority of zoo and aquarium visitors actually arrive at the site with the motivation to learn (Roe and McConney ).…”
mentioning
confidence: 99%
“…With more than 700 million annual visits (Gusset and Dick 2011), as well as an explicit commitment to providing environmental education (Barongi et al 2015), the world's zoos and aquariums are well positioned to contribute to achieving this target ( Figure 1). Indeed, recent studies have demonstrated the potential educational impacts of these institutions (eg Jensen 2010, 2015;Jensen 2014). Additionally, the majority of zoo and aquarium visitors actually arrive at the site with the motivation to learn (Roe and McConney 2015).…”
mentioning
confidence: 99%
“…Under 'Strategic Goal A: Address the underlying causes of biodiversity loss by mainstreaming biodiversity across government and society', Target 1 states that 'By 2020, at the latest, people are aware of the values of biodiversity and the steps they can take to conserve and use it sustainably'. Zoos and aquariums have never been in a better position to contribute to meeting this target with well-crafted conservation-education programmes where people connect with, experience and consequently care about biodiversity Jensen, 2014;Moss et al, 2015). To support this notion further, I reconstructed the famous conservation statement made by Baba Dioum in 1968, to reflect the change in the thinking around the process that motivates people to take action for conservation.…”
mentioning
confidence: 99%